2016
DOI: 10.1007/s11999-016-4892-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Social Support Associated With Upper Extremity Disability?

Abstract: Background Pain intensity and disability correlate with psychosocial factors such as depression and pain interference (the degree to which pain interferes with activities of daily living) as much or more than pathophysiology in upper extremity illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…With the current healthcare climate requiring proof of patient-centered care [31,33,35,38,42,43], efforts to understand and meet patient expectations potentially carry greater impact than currently used objective metrics. Because the ability of our profession to measure the quality and effectiveness of treatment is an evolving and imperfect science, identifying the factors associated with a spectrum of patient expectations allows providers to recognize patients whose pretreatment characteristics may be asynchronous with the projected treatment results.…”
Section: Patientsmentioning
confidence: 99%
“…With the current healthcare climate requiring proof of patient-centered care [31,33,35,38,42,43], efforts to understand and meet patient expectations potentially carry greater impact than currently used objective metrics. Because the ability of our profession to measure the quality and effectiveness of treatment is an evolving and imperfect science, identifying the factors associated with a spectrum of patient expectations allows providers to recognize patients whose pretreatment characteristics may be asynchronous with the projected treatment results.…”
Section: Patientsmentioning
confidence: 99%
“…9,11,13,18,19 Menendez observed that 51% of variability in the qDASH was explained by differences in PROMIS PI CAT scores among new or follow-up hand surgery patients at an urban academic medical center, and furthermore reported a large correlation between PROMIS PI and qDASH scores and medium correlation between PROMIS depression CAT and qDASH scores. 19 Nota observed that pain interference had a strong influence on qDASH variability in a similar patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…19 Nota observed that pain interference had a strong influence on qDASH variability in a similar patient cohort. 11 Three months following hand fracture surgical treatment, Roh observed that Pain Catastrophizing Scale (PCS) scores correlated with increased disability on the qDASH. 18 Interestingly and without a clear explanation, these correlations were absent at the six month postoperative visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]13 This work represents a prospective, longitudinal study of a focused cohort of isolated elbow fractures assessed from first orthopedic review after the emergency department to several months after injury. 37,48 We aimed to identify the demographic, injury, psychological, and social factors associated with limitations 6-9 months after elbow fractures using the WHO International Classification of Disability, Functioning and Health as a framework for organizing these variables (Fig. 2).…”
Section: Q7mentioning
confidence: 99%